Pengembangan E-Modul Pendidikan Agama Islam Interaktif Berbasis Flipbook untuk Meningkatkan Pembelajaran di Sekolah Menengah Pertama - Pribowo, M. Agung; Hadiati, Eti; Koderi; Sufian, Muhammad (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2024)
This study aims to develop, assess feasibility, analyze responses, and evaluate the effectiveness of Flipbook-based Interactive Islamic Religious Education E-Modules to improve learning in Junior High School. This research uses the Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data were collected through observation, interviews, documentation, as well as pre-test and post-test, and the data were analyzed using t-test to measure the effectiveness of the developed media. The results showed that the development of Flipbook-based interactive Islamic religious education e-modules to improve learning in junior high schools using the ADDIE model was effective in improving student learning outcomes. Validation by material experts gave a score of 81.25%, and by media experts 87.5%. The average student response was 86.33%. The t-test results (the calculated t value of 44.737 compared to the t table value of 2.069) showed the effectiveness of the module. Based on these results, the e-module developed is considered feasible and effective for improving Islamic Religious Education learning outcomes.